Bagam script - Rovenchak, Andrij (AAeO - Afrikanistik-Aegyptologie-Online, 2009)
The Bagam (Eghap) script from the Grassfields region of Cameroon is briefly analyzed. An attempt to identify the phonetic values of some Bagam characters is made and some similarity with the Bamum script is reported.